Pengaruh Kepuasan Kerja dan Budaya Organisasi terhadap Kinerja Guru SD Muhammadiyah 6 dan SD Islam Al- Husnayaini Pekanbaru - Mira Santika; Hartono; Muslim Afandi (Global Action and Education for Society, 2025)
This study aims to examine the Influence of Job Satisfaction and Organizational Culture on the Performance of Teachers at Muhammadiyah 6 Elementary School and Al-Husnayaini Islamic Elementary School Pekanbaru. The population and sample in this study were taken from 32 educators, 19 in Muhammadiyah 6 Elementary School Pekanbaru, and 13 in Al-Husnayaini Islamic Elementary School Pekanbaru, so the number of samples in this study was 32 teachers. Data collection in the study was carried out using Observation, Questionnaire, and Documentation techniques. Data Analysis Techniques using multiple regression statistics. Research Results The statistical t-test for job satisfaction on teacher performance produced a t count of 8.929 and a t-table value of 2.042 (significance level 5%, n = 32). If both are compared, then the t count is greater than the t table (8.929> 2.042). This shows that the influence of job satisfaction on teacher performance is 57.6% meaningful or significant. The statistical t-test for the organizational culture variable produced a t count of 5.214 and a t-table value of 2.042 (significance level 5%, n = 32). If both are compared, then the t count is greater than the t table (5.214> 2.042). This shows that the influence of Organizational Culture on Teacher Performance by 31.7% is meaningful or significant. The results of the F test that the F count value is 26.611. When compared with the F table value at a significance level of 5% which is 3.29, then the F count value is greater than the F table (26.611> 3.29). This shows that the influence of Job Satisfaction and Organizational Culture has a positive effect on Teacher performance by 71.6% meaningful or significant. It can be concluded that there is an Influence of Job Satisfaction and Organizational Culture on Teacher Performance at Muhammadiyah 6 Elementary School and Al-Husnayaini Islamic Elementary School Pekanbaru.